Answer:
Step-by-step explanation:
The point-slope form of an equation of a line:
[tex]y-y_1=m(x-x_1)[/tex]
m - slope
(x₁, y₁) - point on a line
We have
[tex]m=6,\ (-1,\ 3)\to x_1=-1,\ y_1=3[/tex]
Substitute:
[tex]y-3=6(x-(-1))[/tex]
[tex]y-3=6(x+1)[/tex]
Convert to the standard form Ax + By = C:
[tex]y-3=6(x+1)[/tex] use the distributive property a(b + c) = ab + ac
[tex]y-3=6x+6[/tex] add 3 to both sides
[tex]y=6x+9[/tex] subtract 6x from both sides
[tex]-6x+y=9[/tex] change all signs
[tex]6x-y=-9[/tex]